Efficacy of the Angiotensin-Converting Enzyme Inhibitors in a Pakistani Hypertensive Cohort and its Associations with Genetic Variation in SCLO1B1 Gene (Precision Medicine Communications, 2024)
A significant proportion of individuals at high risk of cardiovascular risks are prescribed Angiotensin-converting enzyme inhibitors (ACEIs). This study investigated the potential link between SLCO1B1 genetic variations and the effectiveness of ACEIs in managing hypertension within a Pakistani cohort. Designed as a prospective cohort study, it was conducted at a tertiary care hospital, enrolling 83 patients through a convenient sampling approach. After informed consent, 2 mL of blood was withdrawn from each participant. After the DNA extraction from blood samples, single nucleotide polymorphisms (SNPs) in the SLCO1B1 gene were determined through partial sequencing. Furthermore, a structured questionnaire was employed to gather data. The findings indicated a notable reduction in both systolic blood pressure (SBP) and diastolic blood pressure (DBP) following two weeks of ACEI therapy. However, no significant correlation was detected between ACEI efficacy and the two SNPs examined in this population. Expanding this research to larger and more genetically diverse cohorts could provide a clearer understanding of the association between genetic variants and ACEI therapeutic response.
Keywords: Angiotensin converting enzyme; hypertension; genetic polymorphism; SCLO1B1; therapeutic response